The Correlation between Students Reading Habit and Their Writing Ability of Narrative Text - Muhammad Taufik Ihsan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The researcher’s conducted a research at State Islamic Senior High School 1 Pekanbaru. The formulation the problems are : How is the students reading habit? How is the students’ ability of writing narrative text? Is there any significant correlation between students reading habit and their ability in writing narrative text? The design of this reseach study was correlational research. The total number of population was 262 students. The researcher used purposive sampling by taking only one class as sample 34. To analyze the data, the researcher used questionnaire and written test. Questionnaire is used to collect the data about students reading habit. The written test of narrative text was intended to find out students writing ability of narrative text. Based on data analysis, the writer found that the average score of the students’ questionnaire for students reading habit is 60.1. it is categorized into good level. students writing ability is 72.4, the score is categorized good level. the correlation between students reading habit and their ability of writing applied to the sample is 0.629, and consulting to the critical values of the r Product Moment with 95% confidence level and the number of subjects 34 was 0.339. Therefore, the writer concludes that there is a significant positive correlation between students reading habit (X) and their ability of writing narrative text (Y).